Exposure to tobacco secondhand smoke and its associated factors among non-smoking adults in smoking-restricted and non-restricted areas: findings from a nationwide study in Malaysia - Lim, KH; Teh, CH; Mohamed, MHN; Pan, S; Ling, MY; Yusoff, MFM; Hassan, N; Baharom, N; Dawam, ND; Ismail, N; Ghazali, SM; Cheong, KC; et al. (Bmj Publishing Group, 2024)
Objectives Secondhand smoke (SHS) has been associated with increased morbidity and mortality. Therefore, the aims of the paper are to assess SHS exposure among non-smoking adults in Malaysia attending various smoking-restricted and non-restricted public areas according to the Control of Tobacco Product Regulations (CTPR) as well as its relationship with various sociodemographic variables. Design Data were extracted from a cross-sectional study, the Global Adults Tobacco Survey (CATS) 2011 which involved 3269 non-smokers in Malaysia. Data was obtained through face-to-face interviews using a validated pre-tested questionnaire. Factors associated with exposure to SHS were identified via multivariable analysis. Results The study revealed that almost two-thirds of respondents were exposed to SHS in at least one public area in the past 1 month, with a significantly higher exposure among males (70.6%), those with higher educational attainment (81.4%) and higher income (quintile 1%-73.9%). Besides, the exposure to SHS was almost four times higher in non-restricted areas compared with restricted areas under the CTPR (81.9% vs 22.9). Multivariable analysis revealed that males and younger adults at non-restricted areas were more likely to be exposed to SHS while no significant associated factors of SHS exposure was observed in restricted areas. Conclusions The study revealed the prevalence of SHS exposure was higher among Malaysian adults. Although smoke-free laws offer protection to non-smokers from exposure to SHS, enforcement activities in restricted areas should be enhanced to ensure strict public abidance. In addition, legislation of restricted areas should also be extended to greatly reduce the SHS exposure among non-smokers in Malaysia.